Oligomycins as inhibitors of K-Ras plasma membrane localisation. Issue 2 (13th November 2015) - Salim, A. A.; Tan, L.; Huang, X.-C.; Cho, K.-J.; Lacey, E.; Hancock, J. F.; Capon, R. J.
Abstract : Rare oligomycins from soil-derived Streptomyces are low nM inhibitors of K-Ras plasma membrane localisation. Abstract : Frequently present in pancreatic, colorectal and non-small cell lung carcinomas, oncogenic mutant K-Ras must be localised to the plasma membrane (PM) to be functional. Inhibitors of K-Ras PM localisation are therefore putative cancer chemotherapeutics. By screening a microbial extract library in a high content cell-based assay we detected the rare oligomycin class of Streptomyces polyketides as inhibitors of K-Ras PM localisation. Cultivation and fractionation of three unique oligomycin producing Streptomyces strains yielded oligomycins A–E (1–5 ) and 21-hydroxy-oligomycin A (6 ), together with the new 21-hydroxy-oligomycin C (7 ) and 40-hydroxy-oligomycin B (8 ). Structures for1–8 were assigned by detailed spectroscopic analysis. Cancer cell viability screening confirmed1–8 were cytotoxic to human colorectal carcinoma cells (IC50 > 3 μM), and were inhibitors of the ABC transporter efflux pump P-glycoprotein (P-gp), with5 being comparable in potency to the positive control verapamil. Significantly, oligomycins1–8 proved to be exceptionally potent inhibitors of K-Ras PM localisation ( E max 0.67–0.75 with an IC50 ∼ 1.5–14 nM).